2021
DOI: 10.3389/fcomm.2021.613794
|View full text |Cite
|
Sign up to set email alerts
|

Misconceptions, Misinformation and Politics of COVID-19 on Social Media: A Multi-Level Analysis in Ghana

Abstract: Background: Ghana developed an Emergency Preparedness and Response Plan (EPRP) in response to the Severe Acute Respiratory Syndrome Coronavirus (SARS CoV-2) pandemic. A key strategy in the EPRP is to mobilize national resources and put in place strategies for improved risk and behavioral change communication. Nonetheless, concerns have been raised on social media about COVID-19 misinformation and misconceptions. This study used social media content to determine the types, forms and the effects of the myths, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…With the increasing use of social media and other sources of information, feeding them with accurate information from those trusted sources would increase the booster acceptability and help accurate health information to reach more people who are more likely not to get the official and scientific sources of information. This is supported by a previous study that found that sharing trustworthy information through social media by healthcare professionals and institutions, partnering with social media platforms, and establishing a team assigned to debunk misinformation and share accurate information using social media was more effective than trying to direct the general population to institutional websites and scientific publications [ 31 , 32 , 33 ]. In addition, the uptake of the vaccine booster dose can be increased by a collaboration between the public and private sectors, enabling Saudi Arabia to reach herd immunity quickly.…”
Section: Discussionsupporting
confidence: 63%
“…With the increasing use of social media and other sources of information, feeding them with accurate information from those trusted sources would increase the booster acceptability and help accurate health information to reach more people who are more likely not to get the official and scientific sources of information. This is supported by a previous study that found that sharing trustworthy information through social media by healthcare professionals and institutions, partnering with social media platforms, and establishing a team assigned to debunk misinformation and share accurate information using social media was more effective than trying to direct the general population to institutional websites and scientific publications [ 31 , 32 , 33 ]. In addition, the uptake of the vaccine booster dose can be increased by a collaboration between the public and private sectors, enabling Saudi Arabia to reach herd immunity quickly.…”
Section: Discussionsupporting
confidence: 63%
“… 16 Another challenge is the politicisation of come members of the scientific community in the response to COVID‐19. 17 This practice has resulted in the dissemination of conflicting information on the COVID‐19 disease 17 as well as vaccines among members of the scientific community with political affiliations. This was also evidenced in the 2014 EVD vaccine trial in Ghana which undermined the rollout.…”
Section: Engaging the Scientific Communitymentioning
confidence: 99%
“…This needs to be acknowledged to minimise vaccine hesitancy which has been widely reported across West Africa 16 . Another challenge is the politicisation of come members of the scientific community in the response to COVID‐19 17 . This practice has resulted in the dissemination of conflicting information on the COVID‐19 disease 17 as well as vaccines among members of the scientific community with political affiliations.…”
Section: Engaging the Scientific Communitymentioning
confidence: 99%
“…Facebook, Twitter, YouTube, blogs, LinkedIn, Google Plus, WhatsApp, Telegram, mobile apps, news sites, and other online platforms are all popular. Because of its widespread adoption and use of social media, this platform is ideal for disseminating myths, misinterpretations, misconceptions, and misinformation about Covid-19 (Tabong & Segtub, 2021). People who prefer to get information from the government showed higher levels of compliance (Morales-Vives et al, 2022).…”
Section: Relationship Between Misinterpretation Of Information and No...mentioning
confidence: 99%